Novel brominated flame retardants in food composites and human milk from the Chinese Total Diet Study in 2011: Concentrations and a dietary exposure assessment. (November 2016) - Shi, Zhixiong; Zhang, Lei; Li, Jingguang; Zhao, Yunfeng; Sun, Zhiwei; Zhou, Xianqing; Wu, Yongning
Abstract: On the basis of the fifth Chinese total diet study (TDS) performed in 2011, the dietary exposure of the Chinese population to novel brominated flame retardants (NBFRs) was assessed. Six NBFRs were determined in 80 composite samples from four animal origin food groups and 29 pooled human milk samples. Based on gas chromatography-negative chemical ionization mass spectrometry (GC-NCI/MS) analysis, the levels of the total NBFRs ranged from < LOD to 70.2 ng/g lipid weight (lw) in food composites and from 2.48 to 23.9 ng/g lw in human milk samples. Decabromodiphenyl ethane (DBDPE), with mean levels of 9.03 ng/g lw in food composites and 8.06 ng/g lw in human milk, was the most abundant compound in the total NBFRs. No obvious spatial distribution patterns in China were observed in food samples or human milk. The average estimated daily intake (EDI) of total NBFRs via food consumption for a "standard Chinese man" was 4.77 ng/kg bodyweight (bw)/day, with a range of 0.681 to 18.9 ng/kg bw/day. Meat and meat products were the main dietary source of NBFRs, although levels of NBFRs in aquatic food were found to be the highest among the four food groups. The average EDI of total NBFRs for nursing infants was 38.4 ng/kg bw/day, with a range of 17.4 to 113 ng/kg bw/day, which was approximately eight-fold higher than the EDI for adults, suggesting the heavy body burden of NBFRs on nursing infants. The levels and EDI of DBDPE in the present study were similar to or higher than those of legacy BFRs (i.e., PBDEs and HBCD) in the TDS 2007, indicating that DBDPE, as a main alternative to PBDEs, might have become the primary BFR used in China. Highlights: Six novel BFRs were measured in food composites and pooled human milk samples collected from 20 provinces of China DBDPE has become one of the mainly used BFRs in China with levels higher than PBDEs in foods and human milk The dietary intake of NBFRs via human milk for nursing infants was much higher than that for adults